Virus diseases of pigeonpea - Kumar, P. Lava; Jones, A.T.; Farid, W. (2008)
Pigeonpea (Cajanus cajan) is a very important grain legume grown predominantly in the Indian subcontinent, Southern and Eastern Africa and Central America. About 15 viruses and 4 virus-like diseases are reported on pigeonpea. However, only Sterility mosaic disease (SMD) caused by Pigeonpea sterility mosaic virus (PPSMV) is widespread and economically important. Yellow mosaic disease (YMD) caused by legume-infecting begomoviruses (mostly Mungbean yellow mosaic virus, MYMV) is of minor importance. Information is limited with regard to the distribution, epidemiology and economic losses caused by other virus infections in pigeonpea. PPSMV, transmitted by the eriophyid mite, Aceria cajani, is recognized only in pigeonpea-growing countries of Asia. This virus has novel properties with similarities in transmission and cytopathology with the eriophyid mite-transmitted High Plains virus and the agents of unidentified etiology associated with rose rosette, fig mosaic and other similar diseases. YMD is caused by MYMV and other legume-infecting begomoviruses, such as Rhynchosia mosaic virus and Tomato leaf curl New Delhi virus. YMD incidence is usually low and mostly occurs at the time of crop maturity and in pigeonpea sown during off-seasons. An overview of virus diseases of pigeonpea with particular emphasis on SMD and YMD is presented in this chapter.